2005
DOI: 10.1161/01.cir.0000155239.46511.79
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Transfer of Human Placental Ectonucleoside Triphosphate Diphosphohydrolase to Vascular Smooth Muscle Cells Suppresses Platelet Aggregation In Vitro and Arterial Thrombus Formation In Vivo

Abstract: Background-Platelet-rich thrombus formation is a critical event in the onset of cardiovascular disease. Because ADP plays a significant role in platelet aggregation, its metabolism is important in the regulation of platelet activation and recruitment. Ectonucleoside triphosphate diphosphohydrolase (E-NTPDase) is a key enzyme involved in vascular ADP metabolism. We recently isolated 2 isoforms of E-NTPDase from the human placenta. The present study examined whether these isoforms suppress platelet aggregation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Therefore, the pE-NTPDase gene-eluting stent prevents in-stent thrombosis in subacute phase, and may be able to prevent restenosis and late thrombosis by both acceleration of reendothelialization and suppression of neointimal hyperplasia and inflammation. Several recent studies 18,24,25 have indicated effects of E-NTPDase beyond the regulation of platelet aggregation, which support the data of our present study. A mouse model showed that gene transfer of human E-NTPDase into injured arteries inhibited smooth muscle cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the pE-NTPDase gene-eluting stent prevents in-stent thrombosis in subacute phase, and may be able to prevent restenosis and late thrombosis by both acceleration of reendothelialization and suppression of neointimal hyperplasia and inflammation. Several recent studies 18,24,25 have indicated effects of E-NTPDase beyond the regulation of platelet aggregation, which support the data of our present study. A mouse model showed that gene transfer of human E-NTPDase into injured arteries inhibited smooth muscle cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…This protein also inhibits platelet aggregation induced by platelet agonists or shear stress. 16,17 Recently, Furukoji et al 18 reported that human pE-NTPDase gene transfer to air-injured arteries via adenovirus vector suppressed platelet aggregation, thrombus formation, and neointimal growth in mice. Based on these findings, we speculate that local delivery of the pE-NTPDase gene through a gene-eluting stent might prevent subacute in-stent thrombosis and neointimal hyperplasia without requiring antiplatelet agents.…”
mentioning
confidence: 99%
“…Furukoji et al, have shown that expression of placental derived CD39 in rat carotid arteries suppresses thrombus formation and also suggest that subsequent neointimal formation may be limited by this manipulation [30]. Our own studies with rat aortic intimal injury suggest that human vascular CD39 up regulation with adenoviral vectors has comparable protective effects [31].…”
Section: Discussionmentioning
confidence: 64%
“…These somewhat puzzling effects may be explained by the desensitization of select P2Y receptors that in the absence of NTPDase activity has the same effect on receptor-signaling events, as would excessive scavenging of nucleotide, when CD39 is upregulated [30,31]. Hence, both knock-out mice null for Cd39 and transgenic mice over expressing CD39 have prolonged bleeding times secondary to platelet dysfunction, predominantly at the P2Y1 receptor level albeit at different pericellular nucleotide levels [21,32].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, transgenic mice expressing human NTPDase1 exhibited impaired platelet aggregation and were protected from thrombosis in a transplantation setting [179]. Moreover, adenovirus-mediated gene transfer of human placental NTPDase1 [91] into vascular smooth muscle cells was found to suppress thrombus formation and subsequent neointimal growth [180]. Similarly, gene transfer of this enzyme via cationic gelatin-coated stents inhibited subacute in-stent thrombosis and in addition suppressed neointimal hyperplasia and inflammation [181].…”
Section: Downstream Signaling Nucleotidesmentioning
confidence: 99%